Community psychology in the local and regional development - Rozas O., Germán (Revista de Psicología, 1994)
The field of social development is in a process of change. A fundamental factor is the modernization of the State. However, modernization in this area has a last name. On the one hand, from the legal point of view, laws and decrees are articulated that give importance to regional development and local development. On the other hand, we speak here of decentralization. These processes generally point to an extension of democracy, which means an increase in power in decision-making and in the implementation of projects from the point of view of the participants themselves. Overcoming poverty as a priority initiative today goes beyond these processes and becomes an area of updating, as it is no longer defined as a lack but rather based on an association with the theme of development. These issues become necessary study objects for Community Psychology, particularly from the perspective of intervention.